'Some people treat you like an alien': Understanding the female athlete experience of belonging on campus. (24th July 2020) - Slaten, Christopher D.; Ferguson, Jonathan K.; Hughes, Hayley A.; Scalise, Dominick A.
Abstract: College athletes across north America are often known on their respective college campuses for their athleticism, and spend a considerable amount of hours weekly engaging in their respective sport through practices, meetings, travelling and meals, to name a few. It is no wonder it is difficult for these students to feel fully engaged and connected on university campuses as students. Female college athletes in particular, who often are not athletes in revenue-generating sports, often feel left behind as students and isolated as athletes. The purpose of the current study was to examine female collegiate athletes' experience with belonging in a university setting. This qualitative inquiry utilised consensual qualitative research to explore 14 female student athletes' experience of belonging on a university campus. The results of the data analysis yielded the following domains or themes: athletic team culture, athletic department culture, campus support and involvement, female athlete identity, and individual athlete experience. The most salient finding was that these female athletes suggested that their sense of belonging on campus was almost exclusively related to their experience as an athlete and their athletic team.